2020
DOI: 10.3389/feart.2019.00354
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Hydrology and Icemelt in Three Nepal River Basins Using the Glacio-Hydrological Degree-Day Model (GDM) and Observations From the Advanced Scatterometer (ASCAT)

Abstract: An assessment of the water supply and its seasonal and annual changes over the century in the High Mountain Asia (HMA) region is of increasing interest due to its potential impact on one-sixth of the global population. In order to understand the changing hydrology and snow and ice melt, we used remotely sensed Advanced Scatterometer (ASCAT) observations of glacier melt (GM) and a distributed and gridded Glacio-hydrological Degree-day Model (GDM) in three river basins: Tamor, Trishuli and Marsyangdi. The GDM-es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…
Fig. 3.Flowchart showing the workflow involved in OGGM (Maussion and others, 2018) and GDM (Kayastha and Kayastha, 2020a; Kayastha and others, 2020b).
…”
Section: Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…
Fig. 3.Flowchart showing the workflow involved in OGGM (Maussion and others, 2018) and GDM (Kayastha and Kayastha, 2020a; Kayastha and others, 2020b).
…”
Section: Modelsmentioning
confidence: 99%
“…Climate-induced cryospheric changes such as glacier retreat and decrease in snow cover extent can largely influence the timing, magnitude and distribution of seasonal discharge in the river system (Alford and Armstrong, 2010; Immerzeel and others, 2013; Lutz and others, 2014; Kayastha and Kayastha, 2020a; Kayastha and others, 2020b). The cryospheric regime has been enduring drastic alterations since the last few decades and those changes are mainly associated with increasing temperature (Liu and Chen, 2000; Xu and others, 2009; Radić and others, 2013; Shea and others, 2015; Bolch and others, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…These simple TI algorithms yielded reasonable estimates for open sites with shorter vegetation (O1 and O2) but not at forested sites (M1, M2 and M3). Several previous studies reported similar limitations and proposed modifications to TI algorithms that included supplemental variables or processes such as solar radiation [3,29,31,65], variable melt factor [3,31,[34][35][36], cold content [3,32,50], and other forest factors that lower the melting rate beneath the canopy [3]. A similar path was explored here, exploiting the best performing TI algorithm (A1) in a second phase by including these additional variables/processes.…”
Section: Discussionmentioning
confidence: 96%
“…Snow models can be organized into two main categories: energy balance (EB) models [12][13][14]16,[25][26][27] and temperature-index (TI) models [3,[28][29][30][31][32][33][34][35][36]. They all aim to estimate how the snow water equivalent (SWE), which ultimately affects streamflow dynamics, evolves throughout winter.…”
Section: Introductionmentioning
confidence: 99%
“…Based on comparisons with SEB modeling, and the physical basis of SAR measurements we have a high degree of confidence in our methodology and in the ability of the SAR backscatter to detect melting and in data-poor regions such as HMA remote sensing records of this type provide vital information supporting the understanding of surface melt on mountain glaciers. This is crucial to understand SEB on glacier and associated links to climate and downstream hydrological and ecological processes (Kayastha, Steiner et al 2019). Figure AR1.…”
Section: Ar3mentioning
confidence: 99%